MicroRNA-Regulated Proinflammatory Cytokines in Sarcopenia - Jingjing Fan; Xianjuan Kou; Yi Yang; Ning Chen (Hindawi Limited, 2016)
Sarcopenia has been defined as the aging-related disease with the declined mass, strength, and function of skeletal muscle, which is the major cause of frailty and falls in elders. The activation of inflammatory signal pathways due to diseases and aging is suggested to reveal the critical impact on sarcopenia. Several proinflammatory cytokines, especially interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α), play crucial roles in modulation of inflammatory signaling pathway during the aging-related loss of skeletal muscle. MicroRNAs (miRNAs) have emerged as the important regulators for the mass and functional maintenance of skeletal muscle through regulating gene expression of proinflammatory cytokines. In this paper, we have systematically discussed regulatory mechanisms of miRNAs for the expression and secretion of inflammatory cytokines during sarcopenia, which will provide some novel targets and therapeutic strategies for controlling aging-related atrophy of skeletal muscle and corresponding chronic inflammatory diseases.